Roles and Research Trends of Neuroscience on Major Information Systems Journal: A Bibliometric and Content Analysis - Lin, Chien-Liang; Chen, Zezhou; Jiang, Xinyue; Chen, Guan Lin; Jin, Peiqi (Frontiers in Neuroscience, 2022)
Over the past decade, Neuroscience has been integrating into Information Systems to study and solve related problems as a new methodology and perspective. NeuroIS, therefore, has emerged and became a new cutting-edge research field. This review aims to identify, summarize and classify existing NeuroIS publications through a knowledge mapping and the bibliometric analysis. In order to effectively understand the development trend of NeuroIS, this study refers to the journal selection index of Association of Business Schools in 2021, and journals above three stars in the field of information management as the main selection basis. A total of 99 neuroscience papers and their citation data were included in 19 major information system journals of SCI/SSCI. This study analyzes the bibliometric data from 2010 to 2021 to reveal the most productive countries, universities, authors, journals, and prolific publications in electronic marketing. To this end, VOSviewer software was used to visualize the mapping based on co-citation, bibliographic coupling and co-occurrence. In addition, highly used keywords in every 5 years were extracted to demonstrate the research hotspots accordingly. It signifies the evolution of the research field and may reveal the potential research directions in the near future. Moreover, a co-citation network analysis was conducted to help understand how the papers, journals, and authors in the field were connected and related, as well as identify the seminal or pioneering or major literatures. For researchers, network maps visualized research mainstreams and provide a structural understanding of NeuroIS. The review concludes by discussing potential research topics in the field.